6+2xy=4

Simple and best practice solution for 6+2xy=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+2xy=4 equation:


Simplifying
6 + 2xy = 4

Solving
6 + 2xy = 4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 2xy = 4 + -6

Combine like terms: 6 + -6 = 0
0 + 2xy = 4 + -6
2xy = 4 + -6

Combine like terms: 4 + -6 = -2
2xy = -2

Divide each side by '2y'.
x = -1y-1

Simplifying
x = -1y-1

See similar equations:

| 52-(3c+4)=4c+6+c | | 8x^2+45x-450=0 | | 2x^2+8x=3x+48 | | y=4ln(x)+10 | | x^2-20x+50=90 | | -5+18=-77 | | 51/2/2= | | n-17=31 | | x^3-8x^2+27x-163=0 | | 13+3x=6x+19 | | 12x-5=17x-10 | | 6x+40=100 | | 16r^2-8r-1=0 | | X+386000=2512000 | | X+388000=2520000 | | 2x+(9x-4)=18 | | 6.8x-3=5.8x | | 2m-7.5=5.8 | | X*386000=2512000 | | 3(5f+6)= | | X=-1-1*2 | | 8-4z=20 | | 4(z+7)-(2z-1)=z | | 8x-2x(x-9)=2(x-5)+1 | | X=-1-1*-1 | | 2/x-3=26/x | | 4(z+7)-(2x-1)=z | | 4c^2+19c-21=0 | | X=-8-1*-1 | | 16-(4M+8)=5+4M-13 | | (-1)-2*6= | | X=-8-y |

Equations solver categories